2010
DOI: 10.1007/s11136-010-9748-8
|View full text |Cite
|
Sign up to set email alerts
|

Smoking habits and health-related quality of life in a rural Japanese population

Abstract: The results suggested the possibility that in Japan, where smoking prevalence is still relatively high, smokers may be less sensitive to sub-clinical deterioration in their own health status than smokers in Western countries that already have experienced the major decline in their smoking rate. The importance of having the smoker become more sensitive to the sub-clinical adverse effects of cigarette smoking should be stressed for the success of smoking control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 15 publications
4
19
0
1
Order By: Relevance
“…This study also found that the respondents’ MCS scores were higher than their PCS scores, in contrast to findings from most previous studies in China [12,16,17], which focused on urban areas, but similar to those from several earlier studies in Shanghai [6], Japan [28], India [29] and Australia [30] that included some participants from rural areas. The Shanghai study also showed that whether participants were from rural areas was significantly related to RP, BP and MH [6] with people in urban areas reporting higher stress levels than those in rural areas.…”
Section: Discussionsupporting
confidence: 82%
“…This study also found that the respondents’ MCS scores were higher than their PCS scores, in contrast to findings from most previous studies in China [12,16,17], which focused on urban areas, but similar to those from several earlier studies in Shanghai [6], Japan [28], India [29] and Australia [30] that included some participants from rural areas. The Shanghai study also showed that whether participants were from rural areas was significantly related to RP, BP and MH [6] with people in urban areas reporting higher stress levels than those in rural areas.…”
Section: Discussionsupporting
confidence: 82%
“…The SF-36v2 is a standardized international 36-item self-administered questionnaire that was translated, adapted, and validated for use in Japan [26]. This measures eight QOL domains of health status: physical functioning (PF), role physical (RP), bodily pain (BP), general health perception (GH), vitality (VT), social functioning (SF), role emotional (RE), and mental health (MH).…”
Section: Methodsmentioning
confidence: 99%
“… List of relevant studies exploring the association between HRQoL and smoking status [11,45,46,49-55,60-63]. …”
Section: Supplementary Materialsmentioning
confidence: 99%